Role of immunohistochemistry in the era of genetic testing in MYC-positive aggressive B-cell lymphomas: a study of 209 cases. Issue 3 (25th August 2015) - Agarwal, Rishu; Lade, Stephen; Liew, Danny; Rogers, Toni-Maree; Byrne, David; Feleppa, Frank; Juneja, Surender; Westerman, David A
Abstract : Aims: MYC rearrangements with or without BCL2 rearrangements have been shown to be associated with poor prognosis and inferior survival in diffuse large B-cell lymphomas (DLBCL). Most of these cases are still diagnosed by fluorescent in situ hybridisation (FISH) testing, which is expensive, requires expertise and is not routinely available in all laboratories. Immunohistochemistry (IHC) is widely available and has the potential to be used as a screening test to identify cases with increased protein expression and select cases that require confirmatory testing. We correlated the expression of MYC and BCL2 by IHC with FISH studies in an attempt to define a cut-off value, which can be used by laboratories to select cases requiring confirmatory FISH testing. The prevalence of MYC -positive DLBCL and double-hit lymphoma (DHL) has also been studied. Methods: 209 cases comprising of 15 cases of Burkitt lymphoma (BL), 13 cases of intermediate BL/DLBCL and 181 cases of DLBCL were included. IHC and FISH for MYC and BCL2 were performed and the results were correlated. Results: The prevalence of MYC -positive DLBCL and MYC / BCL2 DHL was 13.4% and 7.4%, respectively, in our study. Germinal-centre subtype was more common in MYC -positive DLBCL and DHL. MYC -positive DLBCL also showed higher median Ki-67 (>90%) and CD10 positivity as compared with MYC -negative cases. Conclusions: IHC can be used for screening cases, which require further confirmatory FISH testing. We recommend a cut-off value of ≥30% for MYC by IHC; however, international standardisation of these values is necessary to provide uniformity among laboratories.